A Preclinical Systematic Review and Meta-Analysis of Astragaloside IV for Myocardial Ischemia/Reperfusion Injury - Zheng, Qun; Zhu, Jia-Zhen; Bao, Xiao-Yi; Zhu, Peng-Chong; Tong, Qiang; Huang, Yue-Yue; Zhang, Qi-Hao; Zhang, Ke-Jian; Zheng, Guo-Qing; Wang, Yan (Frontiers in Physiology, 2018)
Astragaloside IV (AS-IV), the major pharmacological extract from Astragalus membranaceus Bunge, possesses a variety of biological activities in the cardiovascular systems. Here, we aimed to evaluate preclinical evidence and possible mechanism of AS-IV for animal models of myocardial ischemia/reperfusion (I/R) injury. Studies of AS-IV in animal models with myocardial I/R injury were identified from 6 databases from inception to May, 2018. The methodological quality was assessed by using CAMARADES 10-item checklist. All the data were analyzed using Rev-Man 5.3 software. As a result, 22 studies with 484 animals were identified. The quality score of studies ranged from 3 to 6 points. Meta-analyses showed AS-IV can significantly decrease the myocardial infarct size and left ventricular ejection fraction, and increase shortening fraction compared with control group (P < 0.01). Significant decreasing of cardiac enzymes and cardiac troponin and increasing of decline degree in ST-segment were reported in one study each (P< 0.05). Additionally, the possible mechanisms of AS-IV for myocardial I/R injury are promoting angiogenesis, improving the circulation, antioxidant, anti-inflammatory and anti-apoptosis. Thus, AS-IV is a potential cardioprotective candidate for further clinical trials of myocardial infarction.